Myelodysplastic Syndrome/Acute Myeloid Leukemia Following the Use of Poly-ADP Ribose Polymerase (PARP) Inhibitors: A Real-World Analysis of Postmarketing Surveillance Data - Zhao, Quanfeng; Ma, Pan; Fu, Peishu; Wang, Jiayu; Wang, Kejing; Chen, Lin; Yang, Yang (Frontiers in Pharmacology, 2022)
Abstract Background and purpose poly-ADP ribose polymerase (PARP) inhibitors show impressive efficacy in a range of tumors. However, concerns about rare and fatal adverse events, including myelodysplastic syndrome (MDS) and acute myelogenous leukemia (AML) have arisen. The aim of this study was to excavate and evaluate the risk of PARP inhibitors causing MDS and AML based on real-word data from two international pharmacovigilance databases. Methods We analyzed adverse event (AE) reports of four PARP inhibitors (olaparib, niraparib, rucaparib and talazoparib) associated with MDS and AML from the United States Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) and EudraVigilance (EV) databases between October 1, 2014, and September 30, 2021, including demographic characteristics, fatality and times to onset. Three different data mining algorithms were used to detect the signals of PARP inhibitors associated with MDS and AML. Results In total, 16710 and 11937 PARP inhibitor AE reports were found in the FAERS and EV databases, of which 332 and 349 were associated with MDS and AML, respectively. The median latencies of MDS and AML associated with PARP inhibitors were 104 (interquartile range [IQR] 16-377) days and 89.5 (IQR 19-401) days, respectively. The average fatality rates of MDS and AML caused by the four PARP inhibitors were 39.23% and 45.39%, respectively, in the FAERS database, while those in the EV database were 32.32% and 34.94%, respectively, the proportion of life-threatening cases in both FAERS and EV database was as high as 30%. Based on the criteria used for the three algorithms, a significant disproportionate association was found between PARP inhibitors as a drug class and MDS and AML. Notably, the risk of MDS was much higher than that of AML. Olaparib appeared to have a stronger association with MDS and AML than did other PARP inhibitors. Conclusion In the real word, PARP inhibitors increase the risk of MDS and AML, which can result in high mortality and tend to occur during long-term use. Our findings provide objective evidence for the postmarketing safety of PARP inhibitors.